Excitation functions of the proton induced nuclear reactions on Zn-nat up to 40 MeV - Khandaker, Mayeen Uddin; Kim, G.N.; Uddin, M.S.; Kim, K.S.; Lee, Y.S. (Elsevier, 2007)
We measured the excitation functions of the Zn-nat(p,xn)Ga-66,Ga-67, Zn-nat(p,pxn)(62,65,69)mZn, and Zn-nat(p,alpha xn)Cu-61 nuclear processes up to 40 MeV by using a stacked-foil activation technique at the MC50 cyclotron of the Korea Institute of Radiological and Medical Sciences. The results were compared with the earlier reported experimental data and theoretical calculations based on the ALICE-IPPE code. We have given new data points for the formation of the above radionuclides. The present values are in good agreement with some well-measured literature values. Integral yields were also deduced from the measured cross-sections. The reported direct measured thick target yields for the formation of the Ga-66 and Ga-67 radionuclides at 22 MeV support our deduced yields. The optimum formation of the Ga-66 and Cu-61 radionuclides with minimum impurities can be obtained at 8-15 MeV and 10-20 MeV energy range, respectively. The yields and decay characteristics of the nuclide Zn-65 are suitable for thin layer activation analysis. (c) 2007 Elsevier B.V. All rights reserved.